Meet with Impact : 40 visual tools for productive meetings and engaging workshops - Russell, Tom (Thomas), 1972- (Pearson Education Limited, 2019)
Tom Russell is Co-Founder and Director of The Facilitation Partnership (TFP) and Inky Thinking. He has 20 years' experience in a variety of large, well known, complex organisations. More recently he has been facilitating meetings across the globe, partnering with clients to achieve breakthrough results in their meetings in companies including Airbus, Mars and SAP.